Relationship between Sports Knowledge, Sports performance and Academic Ability: An Empirical evidence from WAEC Physical Education Results in Oyo State (2007)
The study investigated the relationship between sports knowledge, sports performance and academic ability of individuals that took part in sports activities, with regard to their performance in Physical Education at the Senior School Certificate Examination conducted by WAEC in 2001 and 2002 in Oyo State. The study is an ex-post facto of survey type. The sample consists of 120 participants (85 males and 35 females), with age range of 16 to 20 years. The Pearson product moment correlation test statistics was used for analyzing the data generated in the study. The findings revealed that there is a significant relationship between sports knowledge and sports performance on academic ability of the participants irrespective of their sports knowledge and sports performance. It was recommended, among others, that parents and guardians should encourage their children/ wards to participate in sports.